2023
DOI: 10.1093/mnras/stad1053
|View full text |Cite
|
Sign up to set email alerts
|

Origin and evolution of ultradiffuse galaxies in different environments

Abstract: We study the formation of ultra-diffuse galaxies (UDGs) using the cosmological hydrodynamical simulation TNG50 of the Illustris-TNG suite. We define UDGs as dwarf galaxies in the stellar mass range $\rm {7.5 \le log (M_{\star } / M_{\odot }) \le 9 }$ that are in the $5\%$ most extended tail of the simulated mass-size relation. This results in a sample of UDGs with half-mass radii $\rm {r_{h \star } \gtrsim 2 \ kpc}$ and surface brightness between $\rm {24.5}$ and $\rm {28 \ mag \ arcsec^{-2}}$, similar to defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 141 publications
3
12
0
Order By: Relevance
“…Note that secondary halo properties are also nontrivially correlated with the resulting UDG properties in CDM (e.g.,Benavides et al 2021Benavides et al , 2023.…”
mentioning
confidence: 99%
“…Note that secondary halo properties are also nontrivially correlated with the resulting UDG properties in CDM (e.g.,Benavides et al 2021Benavides et al , 2023.…”
mentioning
confidence: 99%
“…Using 14 Virgo-like clusters from the Illustris TNG100 cosmological hydrodynamical simulation, Sales et al (2020) found two main paths to form cluster UDGs: (a) born UDGs are field low surface brightness galaxies that recently (∼6 Gyr ago median, albeit with significant dispersion) entered the cluster and now show large amounts of dark matter and have stellar populations with intermediate ages and low metallicities, and (b) tidal UDGs are higher surface brightness galaxies that fell into the cluster early on and, as a consequence, have little to no dark matter left, old stellar ages, and high metallicities. Note that born UDGs could correspond to several internal mechanisms discussed in the literature, such as strong feedback (Di Cintio et al 2017;Chan et al 2018) or high-spin halos (Amorisco & Loeb 2016;Benavides et al 2023).…”
Section: Less Extreme Udgs In Virgomentioning
confidence: 96%
“…For instance, in current state-of-the-art cosmological numerical simulations such as TNG50, which models a cosmological volume large enough to include some spread in environment and accretion histories, UDGs are formed via high-spin halos and, to lesser degree, dynamical heating, with the expectation that they all inhabit dwarf-mass dark matter halos (Benavides et al 2023). All other cosmological simulations that include high-density environments find a combination of processes involving feedback and environment, but in not a single case is a failed galaxy compatible with our measurement predicted (Di Cintio et al 2017;Chan et al 2018;Jiang et al 2019;Tremmel et al 2020).…”
Section: Extreme Udgs In Virgomentioning
confidence: 99%
See 1 more Smart Citation
“…Various mechanisms have been proposed to explain the presence of large, diffuse galaxies (as mass-size outliers) across different environments. In the field (i.e., in isolation), their large sizes might be a result of stellar feedback (Di Cintio et al 2017;Chan et al 2018), early galaxy mergers (Wright et al 2021), passing into and out of a more massive halo (socalled backsplash satellites; Benavides et al 2021), or of inhabiting halos with higher spins (Dalcanton et al 1997;Amorisco & Loeb 2016;Liao et al 2019;Mancera Piña et al 2020;Benavides et al 2023; Kong et al 2022). In groups and Original content from this work may be used under the terms of the Creative Commons Attribution 4.0 licence.…”
Section: Introductionmentioning
confidence: 99%